Silica solid particles toughening, strengthening and anti‐aging on epoxy resin. Issue 18 (30th November 2020) - Ai, Jie; Cheng, Wei; Wang, Peng; Qian, Wei; Chen, Qinhui
Abstract: Solid particles used to toughen polymer can induce shear bands and crazing to release the internal stress of polymer. Herein, SiO2 particles with different sizes were prepared by sol–gel method and modified by triethylenetetramine (TETA) in water. 1, 2, 3 and 4 wt% of SiO2 and SiO2 ‐TETA particles are used to toughen epoxy resin (EP). They can form chemical bond with EP to heighten polymer ' s storage modulus and glass transition temperature. SiO2 ‐TETA containing active hydrogen atoms is a better cross‐linking agent than SiO2 . Both SiO2 and SiO2 ‐TETA particles possess obvious strengthening effects on EP. Their toughening effect depends on size. The 100 nm SiO2 nanoparticles showed better toughening performance than 300 or 500 nm SiO2 particles attributing to their higher specific surface area. The impact strength of EP/SiO2 ‐TETA composites with 3 wt% of 100 nm particles is 16.26 kJ/m 2, which is 27.67% and 8.00% higher than EP and EP/SiO2 respectively. In addition, its tensile strength is 63.13 MPa, which is higher than the other is too. The barrier effect of solid particles can effectively improve the heat and ultraviolet resistant properties of EP matrix; as a result, their anti‐aging property is improved significantly. Abstract :